High performance polymers and engineering plastics - Mittal, Vikas (Scrivener, 2011)
This book describes advances in synthesis, processing, and technology of environmentally friendly polymers generated from renewable resources. With contents based on a wide range of functional monomers and contributions from eminent researchers, this volume demonstrates the design, synthesis, properties and applications of plant oil based polymers, presenting an elaborate review of acid mediated polymerization techniques for the generation of green polymers. Chemical engineers are provided with state-of-the-art information that acts to further progress research in this direction.